Methicillin-resistant Staphylococcus aureus pericarditis causing cardiac tamponade. (2019) - Ganji, Maedeh; Ruiz, Jose; Kogler, William; Lung, Joshua; Hernandez, Jarelys; Isache, Carmen
Abstract: Community acquired methicillin-resistant Staphylococcus aureus (MRSA) is an organism that can cause life threatening injuries with 6 cases of purulent pericarditis secondary to MRSA being reported so far. We report a 66 year-old -female who presented to our hospital with a two-week history of worsening shortness of breath, associated with pleuritic chest pain and chills. Patient was found to be positive for influenza type A virus two weeks prior to this presentation, but was never treated. Physical exam upon arrival showed muffled heart sounds and jugular venous distention. Electrocardiogram showed diffuse ST segment elevations along with PR segment depressions in anterolateral leads. She underwent emergent transthoracic echocardiogram that demonstrated a large pericardial effusion most noticeable around the right ventricle with impedance of right ventricle filling. Patient had a pericardial window performed and purulent fluid was drained. Pericardial fluid cultures grew MRSA. Patient was started on vancomycin along with colchicine for MRSA pericarditis and became hemodynamically stable. Pericarditis due to MRSA is extremely rare, especially in the antimicrobial era and in the absence of prior surgical interventions.